Added Value Of Dried Duwo Fish ( Awaous Melanocephalus ) In Donggala District, Central Sulawesi - Ahsan Mardjudo; Hartina Hartina; Fitra Rangga Bayu (Program Studi Budidaya Perairan Universitas Mataram, 2025)
The waters of the Makassar Strait in the Donggala Regency of Central Sulawesi, which is directly opposite the Capital City of the Archipelago (IKN), have the potential for Duwo fish resources as animal food. Duwo fish is included in the Gobiidae family, a type of fish with the highest diversity. In Sulawesi, Awaous melanocephalus is a native species in several areas, in Gorontalo it is known as Nike, in Mamuju, West Sulawesi it is known as Penja fish, and in Central Sulawesi it is known as Duwo fish. Duwo fish can be consumed raw and is generally consumed after being processed and dried. This study aims to analyze the added value of Duwo fish ( Awaous melanocephalus ) in Donggala Regency, Central Sulawesi. Data collection was obtained from Duwo fish processing business actors in Donggala Regency using a purposive sampling research method. Data analysis used the Hayami method of added value analysis. The results of the study showed that the processing of dried duwo fish produced an added value of Rp. 2,500/kg. The ratio of added value obtained with an output of 33.33%, this shows that for every Rp. 100, the added value of dried dowu fish is 33.33 . The processing business of dried duwo fish is one of the forms of business that is pursued by the coastal community of Donggala Regency, Central Sulawesi because it can provide a promising source of income.